Applicability of Plant Extracts in Preclinical Studies of Melanoma: A Systematic Review - Kamylla Rafaella Sena Albuquerque; Nívea Maria Pacheco; Thalia del Rosario Loyo Casao; Fabiana Cristina Silveira Alves de Melo; Rômulo Dias Novaes; Reggiani Vilela Gonçalves (Mediators of Inflammation)
Melanoma is the most aggressive form of skin cancer and arises from melanocyte gene mutation. This disease is multifactorial, but its main cause is the excessive exposure to ultraviolet radiation. Currently, available chemotherapy has shown little expressive results, which may justify the high use of natural products to treat this cancer. We performed a systematic review to compile the results of studies carried out in murine models and investigated the effect of plant extracts on melanoma treatment. Papers were selected in MEDLINE/Pubmed and Scopus according to the PRISM statement. Search filters were developed using three parameters: plant extract, melanoma, and animal model. The 35 identified studies were all submitted to the criteria described in the ARRIVE guidelines. The different extracts showed antiangiogenic, antimetastatic, antioxidant, and anti-inflammatory activity, and also proved to be effective in cell cycle modulation and apoptosis evasion. Bias analysis evidenced the absence of standardized experimental designs, as well as failures in statistical tests and in the presentation of results. The analysis of the studies suggests that the use of plant extracts is effective for the treatment of melanoma in murine models.